Large-area electrodeposited WSe2 over graphene electrodes for optoelectronics - Noori, Yasir J.; Jiapei, Zhang; Muhammad Mustafa, Ahmad Nizamuddin; Thomas, Shibin; Greenacre, Victoria; Zhelev, Nikolay; Ali, Syeda Ramsha; Yisong, Han; Shaokai, Song; Hongwei, Zhang; Graham, Aiden; Abdelazim, Nema M.; et al. (American Chemical Society, 2025)
Integrating graphene and transition metal dichalcogenides (TMDs) into layered material heterostructures brings together the exciting properties that each constituent 2D material offers. However, scaling the growth of graphene-TMD and related heterostructures remains a major challenge. In this work, we demonstrate the use of electrodeposition with a single source precursor (SSP), WSeCl4, to grow few-layer WSe2 using graphene as an electrode. Through characterization via photoluminescence, X-ray photoelectron, and Raman spectroscopy, we show that the electrodeposited WSe2 is stoichiometric and exhibits semiconducting and light-emitting properties. TEM imaging was also performed to show the ordering of the stacked layers of WSe2 over graphene, demonstrating the polycrystalline structure of WSe2. This work paves the way toward utilizing electrodeposition to stack multiple TMDs, including MoS2, WS2, and WSe2 over graphene for electronic and optoelectronic applications.